The Circular Dichroism and the Absolute Configuration of 2,7-Disubstituted Triptycenes - J. Tanaka; F. Ogura; M. Kuritani (CHIMIA)
The absolute configurations of (+)2,7-disubstituted triptycenes are determined by the CD spectral analysis. The result is not in agreement with the absolute configuration determined by the chemical correlation method combined with the X-ray result. This finding provides an additional support to our proposal that the current method of determining the absolute configuration by the X-ray method should be changed so as to give the antipodal configuration.